KANDUNGAN AMONIUM DAN KALIUM TANAH DAN SERAPANNYA SERTA HASIL PADI AKIBAT PERBEDAAN PENGOLAHAN TANAH YANG DIPUPUK NITROGEN DAN KALIUM PADA TANAH SAWAH - Soni Isnaini (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2005)
Tillage system can influence organic matter, nitrogen (N), and potassium (K) in the soil solution. Ammonium (N-NH +) buffer capacity is influenced by K+ in the soil solution. The objective of this study was to determine the content of N-NH + and K exchangeable (K-ex.) and its uptake as well as yield of rice (Oryza sativa L.) in the lowland rice fields under intensive/conventional tillage (CT) and no-tillage (NT) with application of nitrogen (N) and potassium (K) fertilizers. The experiment was conducted during rainy season 1999/2000 (8th growth season) in Kedaloman village, Talangpadang, Tanggamus, Lampung Province. The study was part of long-term research established since dry season 1996. The experiment was set up in a completely randomized block design with three replications. There were three treatments allocated in a factorial arrangement, i.e. (1) tillage system (CT and NT); (2) K fertilizer (without K and 49.8 kg ha-1 K); and (3) N fertilizer (46, 115, and 184 kg ha-1 N). Results of the study showed that N-NH + content and K uptake was affected by the interaction of tillage system, N and K fertilizers. When 49.8 kg ha-1 K was supplied, application of 184 kg ha-1 N produced higher N-NH + content and K uptake than 46 kg ha-1 N on both CT and NT. K-ex. and N uptakes on NT was 18% and 9% higher than those on CT, respectively. Application of nitrogen at 184 kg ha-1 N had the highest effect on K-ex., N uptake, and yield of rice. Application of 49.8 kg K ha-1 produced K-ex.12% higher than without K. In conclusion the N-NH +, K-ex., N and K uptake, and yield of rice were strongly determined by N fertilizer rather than the tillage system or K application.